Maximum Profit Feed Formulation of Broilers: 1. Development of a Feeding Program Model to Predict Profitability Using non Linear Programming - Cerrate, Sandro; Waldroup, Park (International Journal of Poultry Science, 2009)
Maximum Profit Feed Formulation (MPFF) is proposed as a new approach to formulation of broiler diets which predicts the best profit for given ingredient and broiler prices, nutrient requirements and performance. Absolute and relative equations for body weight and feed intake as a function of Dietary Nutrient Density (DND) were developed and included into the objective function of Maximum Profit Programming 3.0. Maximum performance and profitability were compared in terms of DND. Factors such as livability, temperature, processing cost, ingredient and broiler prices, starting and ending broiler prices as well as comparisons of two dynamic models, Body Weight (BW) or cut-up parts (CW), were evaluated to determine changes in DND and to compare the profitability between MPFF and Least-cost Feed Formulation (LCFF). Starter, grower and finisher DND were calculated from the mean of DND obtained by the MPFF. The maximum performances for cut-up parts and body weight were 3.250 and 3.300 ME kcal/g of DND respectively using simulations of the calculated equations, whereas the maximum profits for them were at 3.169 and 3.177 ME kcal/g respectively using the MPFF. Livability slightly decreased the DND, while temperature and processing cost did not affect the DND. However, the ingredient and broiler prices did affect the DND. As broiler meat or corn price increased, the DND was also increased but as the price of soybean meal or poultry oil increased, the DND tended to decrease. For the above variables, use of the MPFF resulted in better profits than did use of LCFF. As expected, the use of ending broiler prices produced better profitability than use of starting broiler prices. If the starting broiler prices were used, the MPFF resulted in higher profits than with LCFF and had similar pattern in profits as ending prices. The dynamic model CW estimated a narrower range of DND compared with those of dynamic model BW. Both dynamic models were more profitable than those of the LCFF model. Starter, grower and finisher DND decreased as the bird aged. This new formulation method can be used to complement least cost formulation to get the best profitability and is recommended for Ross male lines (on which the performance data was developed) with the static nutrient requirement and ingredients used. Requirements for other strains should be quantified by dose-response.